ANALISIS NILAI TAMBAH PADA USAHA AGROINDUSTRI VIRGIN COCONUT OIL (VCO) - Pratiwi, Saskiah; Pellokila, Marthen R.; Kapa, Maximillian M.J. (Undana Press, 2023)
This study aims to (1) calculate the profit from processing coconut into VCO (2) calculate the efficiency (3) calculate the added value of VCO agro-industrial businesses in Kemasama Micro Enterprises. Data collection methods are carried out using profit and loss analysis, R/C ratio analysis and the Hayami method. The results of the research can be explained as follows : (1) the profit received from processing cococnut into VCO in Kemasama Micro Enterprises during 2021 is Rp.42.077.875,-, in 2022 in the amount of Rp.59.703.875,- an increase of Rp.17.626.000,- or 14%. (2) The efficiancy of coconut processing business to become VCO in Kemasama Micro Enterprises with an R/C ratio value of 2,26 in 2021 and an increase in 2022 of 2,62 this means that the business of processing coconut into VCO in Kemasama Micro Enterprises shows efficiency, where the value of the R/C ratio is more than 1 (R/C ratio > 1). (3) The added value obtained from processing cococnut into VCO in the Kemasama Micro Business is Rp.45.000 per one liter of raw material or around 75,84% of the product value per unit of raw material and profit drived from processing coconut into VCO in one production is Rp. 28.312,5,- per liter or 62,22%.